Nest characteristics and populations of Tapanuli Orangutans in the conflict areas, Batangtoru Landscape, North Sumatra, Indonesia - Wanda Kuswanda; R. HAMDANI HARAHAP; HADI S. ALIKODRA; ROBERT SIBARANI (Biodiversitas Journal of Biological Diversity, 2020)
Abstract. Kuswanda W, Harahap RH, Alikodra JS, Sibarani R. 2020. Nest characteristics and populations of Tapanuli orangutans in Batangtoru Landscape, South Tapanuli District, Indonesia. Biodiversitas 21: 3398-3406. Tapanuli orangutan (Pongo tapanuliensis) has been threatened to extinction due to conflicts with humans. Information on the orangutan characteristics in conflict areas at the Batangtoru Landscape is needed. Our research aimed to analyze the characteristics of nests, nest trees, and estimation of orangutan populations in conservation forests and buffer zones to develop conflict mitigation strategies in the Batangtoru Landscape, South Tapanuli District. A line transect method was used to count orangutan nests on 49 transects, starting from June 2019 to January 2020. Data were analyzed with descriptive statistics, frequency tables, Spearman correlation (rho), and the equation by (van Schaick et al. 1995). Tapanuli orangutans make nests at the height of 14.01 meters (90% CI = 13.37-14.67 meters), and most use the main stem as nest support. Tree nests of 35 species (17 families) were identified, with the highest frequency in (Durio zibethinus Murray), especially in the buffer zone. Correlation between nest tree diameter, tree height, and canopy area was significant (p <0.01, n = 83). The estimated orangutan populations in conflict areas were 155 individuals (95% CI = 121-187), and the highest was found in Dolok Sibualbuali Nature Reserve buffer zones. Mitigation strategy of human-orangutan conflict that needs to be realized is the non-cash compensation guaranteeing the community does not disturb orangutans on their land. The compensation forms can be the provision of seedlings and fertilizer for plants, agricultural machinery, knowledge to land management, and orangutan ecotourism development. Nest and feed trees enrichment can be carried out in production forests bordering with conservation area.